Distortions in a multi-level co-financing system: the case of the agri-environmental programme of Saxony-Anhalt - Dieter Kirschke; Astrid Hag̈er; Kurt Jechlitschka; Stefan Wegener (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2007)
In this paper we analyse the impact of the EU multi-level co-financing system on regional policy-making and priority setting taking the case of the agri-environmental programme of Saxony-Anhalt. The implications of several co-financing scenarios are analysed and compared to respective lump-sum transfers using an interactive linear programming approach. The results reveal how regional choices on agri-environmental measures are influenced by the co-financing system leading to distortions. The extent of these distortions depends on the specific regional preferences and restrictions. – – Der Beitrag untersucht den Einfluss der Kofinanzierung innerhalb des Mehrebenensystems der EU auf die regionale Politikgestaltung und Prioritätensetzung anhand des Agrarumweltprogramms Sachsen-Anhalts. Dazu wird ein interaktiver linearer Programmierungsansatz genutzt, mit dem verschiedene Szenarien der Kofinanzierung mit Szenarien verglichen werden, in denen dem Bundesland entsprechende Pauschalbeträge zur Verfügung stehen. Die Ergebnisse zeigen, dass die Entscheidungssituation durch das bestehende System der Kofinanzierung beeinflusst und verzerrt wird. Das Ausmaß der Verzerrung ist abhängig von den spezifischen regionalen Präferenzen und Restriktionen (Quelle: Verlag).
Keywords: 330; EU-Agrarpolitik; Subvention; Politisches System; EU-Staaten; Agrarpolitik; Sachsen-Anhalt; Deutschland; Mathematische Optimierung; Szenariotechnik